CITRA TOKOH WANITA MUSLIMAH DALAM NOVEL BUMI BIDADARI KARYA TAUFIQURRAHMAN AL- AZIZY - Enjel Yolanda Muntipane; Hamidin Hamidin; Bakhtaruddin Nasution (Faculty of Languages and Arts, Universitas Negeri Padang, 2014)
The purpose of this study is to describe the image of the Muslim woman character in the novel Bumi Bidadari written by Taufiqurrahman Al - Azizy. This was a qualitative research with descriptive method based on content analysis. Object of this study was novel Bumi Bidadari written by Taufiqurrahman Al - Azizy. Data analysis was done by (1) classifying the data associated with the image of the Muslim woman, (2) interpreting the data associated with the image of Muslim women, (3) analyzing and inventorying data associated with the image of Muslim women, (4) concluding the data, (5) writing a report. The findings of this research indicate that the image of the Muslim woman in the novel Bumi Bidadari written by Taufiqurrahman Al - Azizy is qanitat, women who are honest and keep his verbal, patient and sincere woman, woman who likes to give alms, woman who are fasting and keep her prayer, women who maintain honor and views, and the women who remember Allah/God remembrance .